«Doomed to Success»: Promoting School Power, Role of the Family, and Inequality on the Way of the Olympiads Winners to University - Chernenko, Svetlana; Romanenko, Ksenia (Voprosy obrazovaniya / Educational Studies Moscow, 2022)
The article proposes to consider the preparation and participation in intellectual contests (Olympiads) for schoolchildren for further admission to selective universities as a specfic type of tracking, the choice of an educational trajectory. The most part of studies of school Olympiads deal either with issues of methodological training of schoolchildren and teachers, or with a comparison of students who got into universities according to the results of the Unified State Exam or the results of Olympiads. This paper closes a gap related to the involvement of schoolchildren into the Olympiad movement and their choice of Olympiads as an admission strategy. The study was conducted in a qualitative methodology: due to semi-structured interviews with students who entered universities according to the results of the All-Russian Olympiad of Schoolchildren (VSOSH), the individual experience of the Olympiad students is reconstructed. The total number of participants of the study is 61 students who represent different areas of the Olympiads and different regions of Russia (graduates of Moscow schools are not specifically included in the sampling because of the active support of Olympiads in the schools of the capital). The results of the study demonstrate the promoting school power, when students receive additional support and encouragement to participate in Olympiads, the conscious choice of Olympiads as an alternative strategy for the admission to universities, the role of teachers, the community of Olympiad participants, and family members in informing about the possibility of participating in Olympiads, as well as related barriers and inequality of access to information and support.